Decision Support on Supply Chain Management System Using Apriori Data Mining Algorithm - Eka Widya Sari; Ahmad Rianto; Siska Diatinari Andarawarih (IC-ITECHS, 2014)
Stock availability and stock completeness is important thing for a shop. Because of that, management process for stock managing is necessary to avoid stock flooding the same product or demand less by consumer. System also help manager to selling optimization high demand product. To solve this problem, need a system that help people to make decision about what kind and how much product should be available for next specific period. Apriori algorithm used to decide relationship between one product and the others. Apriori also used to decide what kind of product is high number of selling to customer. This information is very useful to do supply chain for each product. Criteria that used for determining solution on this system are transaction minimum support, product selling combination and number of selling product. Output resulted by system is alternative solution as percentage selling product and combination of selling product in one transaction. Minimum transaction used for system test is 1000 transaction with 50 kind of product.